Research on gravel packing technology for water control completion in horizontal wells: Quantitative analysis and mathematical representation of flow characteristics - Song Nie; Sujuan Gao; Haitao Li; Meiling Guo; Dandan Yin; Tao Huang; Xiaojiang Cui (Results in Engineering)
Water control gravel packing is widely applied in horizontal well completions for unconsolidated sandstone reservoirs. Although its field effectiveness is recognized, internal flow behavior remains poorly quantified. This study investigates the flow characteristics within the horizontal section of such completions using 15 CFD simulation cases. The effects of six key parameters—including valve number, type, size, spacing, inlet velocity, and fluid type — on flow distribution and pressure drop are evaluated. The results indicate that valves of the same type exhibit consistent flow distribution, whereas configurations involving multiple valve types lead to systematic, type-dependent variations. Valve spacing and inlet velocity have limited influence on flow balance but may affect gravel packing performance. A mathematical model is developed to quantify the relationship between valve flow rate and pressure loss. The findings provide practical guidance for optimizing valve design and configuration in gravel packing operations and for predicting the gravel packing process, while also laying the foundation for the further development of predictive simulation tools.